Through the paths of Museology and Education: Sociomuseology, Citizenship and Cultural Diversity (Cadernos de Sociomuseologia, 2022)
Abstract: This text presents intrinsic relationships between the areas of Museology and Education, based on UNESCO's theoretical framework that underpin these connections. Establishes dialogue with the project “Education for the 21st century”, based on four fundamental pillars for the promotion of the cognitive and social development of human beings; and, it reflects on the impacts of an education based on a new “social contract” that will allow redesigning a future that collectively promotes socio-political-educational-cultural changes. This is an essay on the role and influence of the Brazilian educator Paulo Freire in the field of museology, through educational actions and museological processes socially committed to popular emancipation. Some of the Research, Development and Reciprocity of Knowledge activities carried out by the UNESCO-ULHT Chair “Education, Citizenship and Cultural Diversity” in the year 2021 are presented. how the field of museology has reimagined Freirean praxis in its processes, intervention territories and educational projects.Keywords: Museology, Education, Citizenship, Cultural Diversity, Paulo Freire